2018
DOI: 10.1177/0954410018794317
|View full text |Cite
|
Sign up to set email alerts
|

Design of morphing wing with surface discontinuity

Abstract: Aircraft wing morphing or radical shape change in flight has long been the subject of inquisitive research around the world. It happens because morphing ensures optimal adaptation to any flight conditions such as takeoff , cruise, landing and other manoeuvres. The current state of material engineering is not yet in a position to provide adequate technologies to achieve such significant changes in the wing's shape as morphing requires, though interesting progress can be observed. This article presents a new con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In recent years, a development of new methods of computational fluid dynamics (CFD) has enabled the simulation of many phenomena occurring during the flow of liquids around solid bodies. Proper configuration of specialized numerical codes allowed to analyze complex geometric surfaces or even morphing wings on early stages of the design process like showed in Goraj et al (2018) and Goetzendorf-Grabowski and Tarnowski (2018). Moreover, rapid development of more reliable tools for multiphysics calculations allowed the designers to address more problems at the very beginning or at early stages of the design process.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a development of new methods of computational fluid dynamics (CFD) has enabled the simulation of many phenomena occurring during the flow of liquids around solid bodies. Proper configuration of specialized numerical codes allowed to analyze complex geometric surfaces or even morphing wings on early stages of the design process like showed in Goraj et al (2018) and Goetzendorf-Grabowski and Tarnowski (2018). Moreover, rapid development of more reliable tools for multiphysics calculations allowed the designers to address more problems at the very beginning or at early stages of the design process.…”
Section: Introductionmentioning
confidence: 99%
“…The UAV system “Baltic” was selected as the test platform, built in the weight class up to 25 kg, designed in the flying wing configuration (Figure 1). It is a continuation of the smaller UAV research project with similar geometry, which has been presented in earlier papers (Mieloszyk et al , 2020; Tarnowski et al , 2018). The geometry of the aircraft is the result of a unique numerical optimization framework developed by the authors, which incorporates full flight dynamic stability constraints.…”
Section: Introductionmentioning
confidence: 97%
“…In this paper, for the purpose of mass estimations methods evaluation, two UAV composite structures will be examined. The first one is a 5 kg UAV in the flying wing configuration (Tarnowski et al , 2018) shown in Figure 1. It has a composite structure made with composite wet layup vacuum technology.…”
Section: Introductionmentioning
confidence: 99%